2020
DOI: 10.1080/13696998.2020.1735398
|View full text |Cite
|
Sign up to set email alerts
|

A discrete choice experiment to assess patients’ preferences for HIV treatment in the rural population in Colombia

Abstract: Aim: To elicit patients' preferences for HIV treatment of the rural population in Colombia. Methods: A discrete choice experiment (DCE), conducted in a HIV clinic in Bogot a, was used to examine the trade-off between five HIV treatment attributes: effect on life expectancy, effect on physical activity, risk of moderate side-effects, accessibility to clinic, and economic costs to access controls. Attributes selection was based on literature review, expert consultation and a focus group with six patients. An eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 28 publications
(47 reference statements)
1
25
0
Order By: Relevance
“…Our data comprised of seven studies from the African region [ 34 40 ], 10 in the Americas [ 23 , 41 49 ], five in Europe [ 50 54 ], and one in both the Americas and Europe (USA and Germany) [ 55 ]. Sixteen studies were quantitative [ 23 , 34 , 36 , 38 , 40 , 41 , 43 , 44 , 46 48 , 51 – 55 ] and three were qualitative [ 35 , 39 , 42 ]. Four articles reported both qualitative and quantitative findings [ 37 , 45 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data comprised of seven studies from the African region [ 34 40 ], 10 in the Americas [ 23 , 41 49 ], five in Europe [ 50 54 ], and one in both the Americas and Europe (USA and Germany) [ 55 ]. Sixteen studies were quantitative [ 23 , 34 , 36 , 38 , 40 , 41 , 43 , 44 , 46 48 , 51 – 55 ] and three were qualitative [ 35 , 39 , 42 ]. Four articles reported both qualitative and quantitative findings [ 37 , 45 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Patients’ preferences were elicited with DCE/conjoint analysis method in 12 studies [ 23 , 34 , 36 38 , 40 , 43 , 46 , 48 , 50 , 52 , 54 ]; rating exercise [ 47 , 51 ], ranking exercise [ 49 ] and adaptive conjoint analysis [ 41 , 55 ] in two studies each; and pair-wise comparison [ 45 ], and Best–Worst Scaling 1 [ 44 ] in one study each (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of the Journal of Medical Economics (August 2020), Goossens et al 8 and Sijstermans et al 9 reported on DCEs conducted to assess patients' preferences for HIV treatment in rural and urban Colombia. Five attributes were derived from literature review and a focus group with patients: "effect on life expectancy," "effect on physical activity," "risk of moderate side effects," "accessibility to clinic" and "economic cost to access controls".…”
Section: Colombian Patientsmentioning
confidence: 99%
“…Next to rural versus urban differences, it is important to consider the different modes of administration of ART, which could be delivered orally as well as via injection. The studies of Goossens et al 8 and Sijstermans et al 9 did not include mode of administration, which means that more research is needed to identify potential differences in preferences between modes of administration. Recently, in the Adjuvant Tamoxifen: Longer Against Shorter (ATLAS) and Assessment of ibrutinib plus rituximab in front-line CLL (FLAIR) trials, monthly ART injection was shown to be noninferior to continuing current daily threedrug oral ART 14 .…”
Section: Colombian Patientsmentioning
confidence: 99%